Simplifying criminal lawsuit procedures - SOUIGAT, Ahmed; SOUIGAT, Belkacem (Journal of Human Sciences, 2025)
Countries have known litigation procedures since ancient times, but in a narrow way, as the Pharaohs knew it first, and it was known in the Greek and Roman eras, when litigation procedures before the reconciliation court were simple and quick, and special courts, made up of people other than ordinary judges, were established to look into certain crimes, such as crimes committed in markets and public roads, as the Middle Ages knew that criminal procedures were brief to achieve speed, however, without prioritizing the protection of individual freedom. The primary objective of streamlining criminal procedures is to tackle